2012
DOI: 10.1089/ten.tec.2011.0482
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized Functional Endothelial Progenitor Cell Lines from Umbilical Cord Blood for Vascular Tissue Engineering

Abstract: Endothelial progenitor cells (EPCs) play a significant role in multiple biological processes such as vascular homeostasis, regeneration, and tumor angiogenesis. This makes them a promising cell of choice for studying a variety of biological processes, toxicity assays, biomaterial-cell interaction studies, as well as in tissueengineering applications. In this study, we report the generation of two clones of SV40-immortalized EPCs from umbilical cord blood. These cells retained most of the functional features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The HEPC-CB.1 cell line was obtained from umbilical cord blood [ 19 ] and prepared mainly for in vitro and in vivo studies. A similar line of endothelial cell progenitors was presented in Sobhan's paper with the suggestion of using it in tissue engineering [ 20 ]. The HEPC-CB.1 cell line has features suggesting that it could be used in some new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The HEPC-CB.1 cell line was obtained from umbilical cord blood [ 19 ] and prepared mainly for in vitro and in vivo studies. A similar line of endothelial cell progenitors was presented in Sobhan's paper with the suggestion of using it in tissue engineering [ 20 ]. The HEPC-CB.1 cell line has features suggesting that it could be used in some new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 92%
“…G-CSF [ 17 , 18 ], or isolation of cells from two or more donors. Another possibility to provide a sufficient number of progenitor cells with a well-defined cell type, for basic research and possible clinical use, is their immortalization [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the 6th day, cells were trypsinised and protein was extracted and stored at À80 C until used. Equivalent amounts of total protein (50 μg) were separated by electrophoresis in 12% SDSpolyacrylamide gels (SDS-PAGE) at 70 V and electrophoretically transferred to a polyvinylidene difluoride membrane at 100 V. 24 The membranes were incubated overnight at 4 C with the specific antibodies: mouse anti-rabbit Troponin T2, cardiac type [RV-C2] (Developmental Studies Hybridoma Bank), anti-MyoD1 antibody (Abcam), Anti-Connexin 43/GJA1 antibody [CXN-6] (Abcam). The blots were treated with horseradish peroxidase-conjugated anti-mouse secondary 1:1000 prepared in 0.5 g BSA (Sigma Aldrich) in TBST for 1 h.…”
Section: In Vitro Studies Using H9c2 Cellsmentioning
confidence: 99%
“…Unfortunately, HUVECs often render unstable vessels and their transplantation is capable of inducing an immune response from the host (Baiguera and Ribatti, 2013). Several studies demonstrated that endothelial progenitor cells (EPCs) represent a promising cell population to be used on prevascularized scaffolds (Aronson et al, 2012;Duttenhoefer et al, 2013;Guerrero et al, 2013;Serrano et al, 2011;Sobhan et al, 2012). These cells represent a small population of circulating CD34 + cells with the capacity of accomplishing phenotypical features of ECs in vitro (Asahara et al, 1997;Finkenzeller et al, 2007).…”
Section: Cell Seedingmentioning
confidence: 99%